High-moisture sorghum for growing-finishing swine - M Trotter; G L Allee (Kansas Agricultural Experiment Station Research Reports, 1976)
Eighty-seven crossbred pigs (averaging 95 pounds initially) were used to compare the value of sorghum grain harvested with high-moisture and stored in an oxygen-limiting structure with that harvested with high-moisture and treated with propionic acid (1.2%), and stored in a metal bin, or field dried. Average daily gain, average daily feed intake, and feed/gain ratios in a growth trial and protein and energy digestibilities in a digestion trial, showed that high-moisture sorghum grain and field-dried sorghum have equal feeding values when compared on a dry-matter basis.; Swine Day, Manhattan, KS, November 11, 1976
Keywords: Swine day; 1976; Kansas Agricultural Experiment Station contribution; no. 519-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 283; Swine; High-moisture sorghum; Growing-finishing pigs; Energy digestibilities; Propionic acid